COVID-19 pneumonia: What APRNs should know. Issue 7 (July 2021) - Avadhani, Amita; Cardinale, Maria; Akintade, Bimbola
Abstract : Abstract: COVID-19-associated pneumonia is a complex acute care diagnosis that requires careful evaluation and management. This article includes pertinent recommendations for management of acutely ill patients with COVID-19 pneumonia. Abstract : COVID-19-associated pneumonia is a complex acute care diagnosis that requires careful evaluation and management. This article includes pertinent recommendations for management of acutely ill patients with COVID-19 pneumonia.